Radioprotective effect of chicory seeds against genotoxicity induced by ionizing radiation in human normal lymphocytes - Hosseinimehr, S J; Ghaffari-rad, V; Rostamnezhad, M; Ghasemi, A; Allahverdi Pourfallah, T; Shahani, S (Cellular and Molecular Biology, 2015)
The search for less-toxic radioprotective agents has led to a growing trend towards natural products. Protective effect of the methanolic extract of chicory seeds (MCS) was investigated against genotoxicity induced by ionizing radiation in human lymphocytes. Human peripheral blood samples were collected and incubated with MCS at different concentrations (10, 50, 100, and 200 Î¼g/mL) for two hours. The whole blood samples were exposed in vitro to X-ray at dose 2.5 Gy. Then, the lymphocytes were cultured with mitogenic stimulation to determine the micronucleus in cytokinesis blocked binucleated cell. The methanolic extract at all doses significantly reduced the frequency of micronuclei in binucleated lymphocytes, as compared with similarly irradiated lymphocytes without any extract treatment. The maximum protection was observed at 200 Î¼g/mL of MCS, it completely protected genotoxicity induced by ionizing radiation in human lymphocytes. The extract exhibited a concentration-dependent radical scavenging activity on 1,1-diphenyl-2-picryl hydrazyl free radicals. HPLC analysis of MCS showed this extract is containing chlorogenic acid as a phenolic compound. These data suggest that the radioprotective effect of methanolic extract of chicory seeds can be attributed to the presence of phenolic compounds such as chlorogenic acid which act as antioxidant agents.